(untitled) (LEGAL DIALOGICA, 2025)
This research aims to determine and analyze the legal strength of the Memorandum of Understanding as an agreement document based on the Civil Code, and to understand and analyze the legal protection for the parties in the Memorandum of Understanding as an agreement document based on the Civil Code. This research falls into the category of normative legal research, which is a type of research conducted through the examination of library materials or legal materials. By raising legal issues as a system of norms, this research makes legal norms the main focus of its analysis. The results of this study indicate that the Legal Strength of a Memorandum of Understanding (MoU) as a Document of Agreement, when viewed from the Civil Code, essentially has legal force as a document of agreement if it meets the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. The binding force of the MoU highly depends on the intentions of the parties and the formulation of the clauses outlined in it. In the event of a breach by one party, legal resolution can be pursued through two pathways: non-litigation resolution (negotiation, mediation, or arbitration, if previously agreed upon) and litigation (civil lawsuit in court). The author’s recommendations in this study are suggested to all parties drafting a Memorandum of Understanding (MoU) to formulate the MoU in accordance with the Civil Code regarding the validity requirements of agreements. The MoU should contain a clear statement about its binding nature, as well as clear clauses regarding the rights and obligations of each party, to provide legal certainty. Abstrak: Penelitian ini bertujuan Untuk mengetahui dan menganalisis kekuatan hukum Nota Kesepakatan (Memorandum of Understanding) sebagai suatu akta kesepakatan ditinjau dari Kitab Undang-Undang Hukum Perdata dan Untuk mengetahui dan menganalisis perlindungan hukum terhadap para pihak dalam Nota Kesepakatan (Memorandum of Understanding) sebagai suatu akta kesepakatan ditinjau dari Kitab Undang-Undang Hukum Perdata. Penelitian ini termasuk dalam kategori penelitian hukum normatif, yaitu jenis penelitian yang dilakukan melalui penelaahan terhadap bahan pustaka atau bahan hukum. Dengan mengangkat isu hukum sebagai suatu sistem norma, penelitian ini menjadikan norma hukum sebagai fokus utama dalam analisisnya. Hasil penelitian ini mengindikasikan bahwa Kekuatan Hukum Nota Kesepakatan (Memorandum Of Understanding) Sebagai Suatu Akta Kesepakatan Ditinjau Dari Kitab Undang-Undang Hukum Perdata pada dasarnya memiliki kekuatan hukum sebagai suatu akta kesepakatan apabila memenuhi syarat sah perjanjian sebagaimana diatur dalam Pasal 1320 Kitab Undang-Undang Hukum Perdata (KUHPerdata). Dan kekuatan mengikat MoU sangat bergantung pada intensi para pihak dan rumusan klausul yang dituangkan di dalamnya. Dan dalam hal terjadi wanprestasi oleh salah satu pihak, penyelesaian hukum dapat ditempuh melalui dua jalur, yaitu penyelesaian secara non-litigasi (musyawarah, mediasi, atau arbitrase, bila disepakati sebelumnya) dan secara litigasi (gugatan perdata di pengadilan). Rekomendasi penulis pada penelitian ini disarankan kepada semua pihak yang menyusun Nota Kesepakatan (Memorandum of Understanding) agar menyusun MoU sesuai dengan KUHPerdata tentang syarat sah perjanjian. MoU sebaiknya memuat pernyataan tegas mengenai sifat mengikatnya, serta klausul yang jelas tentang hak dan kewajiban masing-masing pihak, guna memberikan kepastian hukum.